Energy, Environment and COP26 - Ammendola, Giuseppe (2022)
AT NO POINT IN TIME, ARGUABLY, have energy and the environment been as widely perceived as more connected with one another and important to the future of mankind. And the Conference of the Parties (COP) on Climate Change held in Glasgow, UK between October 31 and November 12.